GE_GERICHTE C/9472/2012 vom 27. März 2015 - GE Cour de justice (2015)
COPROPRIÉTÉ; PARTAGE(SENS GÉNÉRAL); OBLIGATION D'ENTRETIEN; CONJOINT; ENFANT; LIQUIDATION DU RÉGIME MATRIMONIAL | CC.122; CC.125; CC.205.2; CC.285